Local Climate Governance in the Global South: The case of eThekwini Municipality and the Responsible Accommodation Campaign. (14th June 2017) - Lervik, Marita; Sutherland, Catherine
Abstract: Local climate governance has become a key focus of the climate change agenda. Much research has been conducted on the topic in northern countries, but more research is needed in the South, where local governments often are less equipped to deal with challenges associated with climate change. This paper discusses different forms of local climate governance, with a specific focus on the relevance of networks. Local climate governance in eThekwini Municipality, South Africa, is used as a case study, particularly focusing on a campaign that was implemented in 2011 before the international climate conference (COP17). The modes of governing in eThekwini are considered through a framework of local climate governing and identified mainly as self‐governing and governing through enabling, the campaign being an example of the latter. The campaign also exemplifies how network governance can shape climate policy and significantly alter a project from initiation to implementation. While networks can contribute to improved communication and information exchange, there may be an inherent risk of private partners having a perverse incentive against implementing effective climate policies due to their own interests in maintaining current structures. It is not clear whether the change from regulative governance to governing by enabling will lead to more effective climate policies in the longer term. More research is required to determine this. While this study is too small to make broader generalizations, it does provide insight into how the introduction of network governance may impact climate governance at the local level in the South. Copyright © 2017 John Wiley & Sons, Ltd and ERP Environment